An Approach for Developing an Optimal Discount Pricing Policy - Lal, Rajiv; Staelin, Richard (Management Science, 1984)
This paper addresses the problem of why and how a seller should develop a discount pricing structure even if such a pricing structure does not alter ultimate demand. The situation modeled is most appropriate where the seller's product does not represent a major component of the buyer's final product, where the demand for the product is derived, or where the price is only one of many factors considered in making a purchase decision. A model of buyer reaction to any given pricing scheme is developed to show that there exists a unified pricing policy which motivates the buyer to increase its ordering quantity per order, thereby reducing the joint (buyer and seller) ordering and holding costs. As a result, the seller is able to reduce its costs while leaving the buyer no worse off and often better off. The model is extended to handle variable ordering and shipping costs and situations where the seller faces numerous groups of buyers, each having different ordering policies. Finally a case study is presented explicitly showing how the proposed pricing policy can be applied to the situation of a large seller selling to a number of different buyer groups.